2017
DOI: 10.1007/s11657-017-0351-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with high 24-month persistence with denosumab: results of a real-world, non-interventional study of women with postmenopausal osteoporosis in Germany, Austria, Greece, and Belgium

Abstract: SummaryPersistence with osteoporosis therapy is vital for fracture prevention. This non-interventional study of postmenopausal women receiving denosumab in Germany, Austria, Greece, and Belgium found that persistence with denosumab remains consistently high after 24 months in patients at high risk of fracture.PurposeContinued persistence with osteoporosis therapy is vital for fracture prevention. This non-interventional study of clinical practice evaluated medication-taking behavior of postmenopausal women rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 40 publications
(82 reference statements)
3
20
0
1
Order By: Relevance
“…Previous persistence studies of denosumab covering the USA, Canada and several European countries excluding the UK have reported persistence at 12 months of 55.9-99.1% and at 24 months of 34.8-99.5% [24][25][26][27][28][29][30][31][32][33][34][35]. In contrast, for other parenteral therapies, the previous studies reported persistence at 12 months of 33.8-74.5%, and for oral therapies reported 10-78% [21,28].…”
Section: Discussionmentioning
confidence: 93%
“…Previous persistence studies of denosumab covering the USA, Canada and several European countries excluding the UK have reported persistence at 12 months of 55.9-99.1% and at 24 months of 34.8-99.5% [24][25][26][27][28][29][30][31][32][33][34][35]. In contrast, for other parenteral therapies, the previous studies reported persistence at 12 months of 33.8-74.5%, and for oral therapies reported 10-78% [21,28].…”
Section: Discussionmentioning
confidence: 93%
“…This duration of treatment is, however, consistent with "real-world" findings showing adherence to Dmab treatment for 2 years in about 50% of patients in most studies, (41)(42)(43)(44)(45) though higher rates have also been reported. (46) In addition, the relatively small number of patients of our study allowed detailed analysis of individual responses, not generally available in large trials, which provided information important for clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its pharmacokinetics, Dmab at the approved dose of 60 mg is administered subcutaneously every 6 months. This intermittent way of administration renders the agent appealing, especially for older patients with polypharmacy, inability to remain in an upright position for long or impaired memory, and it increases the persistence to treatment (51).…”
Section: Efficacymentioning
confidence: 99%